FORGIVENESS MODEL PROFETIK DALAM BANDINGAN STRUKTURAL TEORI KONFLIK - Ali, Syamsuri (Analisis: Jurnal Studi Keislaman, 2014)
THE PROPHETIC “FORGIVENESS” MODEL IN THE STRUCTURE  OF  CONFLICT  THEORY.  This  article  reviews the distinction  of the concept  of “forgiveness”  in the prophetic models compared with the concept of “forgiveness” in the theory of conflict. The argument  is constructed  by reviewing what had been practiced by the Prophet Muhammad PBUH while in Mecca and Medina,  including the text of the Qur’an and the context of the historical reality in the hadith. The study finds out  significant differences between the two models, both in the structural aspects and the procedural. The differences in the structural  aspects are associated with the stages (phases) and orientation,  while  in the procedural aspects are related to the implementation mechanism. In addition, the prophetic “forgiveness” model was implemented in   a   linear   fashion,   whereas  “forgiveness”   in   the   conflict theory  model can be implemented either in a linear  fashion or simultaneously.  The above-mentioned  distinctions indicate  that the prophetic  “forgiveness”  model can be an alternative  to the development  of  conflict resolution  theory. Moreover, besides it can be used as a contribution  to the development of the theory of conflict resolution the prophetic “forgiveness” model can also be used as a basis for strengthening the local wisdom practices in the Muslims society, including in Indonesia.